Effect Of Polymer Concentration On Development Of Asymmetric Polyethersulfone Membrane For Gas Separation - Norida, R.; Ismail, A. F.; Abdul Rahman, W. A. W. (2004)
Asymmetric polyethersulfone (PES) membranes were fabricated through a simple dry/wet phase inversion process. Casting solution developed in this study consisted of polyethersulfone, 1-methyl –2- pyrolidone (NMP) and distilled water. The casting solution was cast using pneumatically-controlled casting machine at constant shear rate and evaporation time. The membranes were characterized by gas permeation with pure O2 and N2 as test gases, while the cross section and surface layer morphologies were examined using Scanning Electron Microscopy (SEM). The results showed that the selectivity of the PES membrane increases with the increasing of polymer concentration. Polymer concentration has been identified as one of the most influential parameter in determining membrane performance as well as producing different morphology. Selectivity of these membranes was relatively higher compared to conventional membranes, some of them even surpassed the intrinsic. Thus, the selectivity of O2/N2 is approximately 7.95, at 32.67 wt % of PES concentration and it is believed that the parameter such as polymer concentration used strongly affects the membrane performance.